Geospatial and multivariate statistical analysis of heavy metal concentration in soils of Perlis / Siti Norbaya Mat Ripin - Mat Ripin, Siti Norbaya (2016)
Urbanisation and industrialization have elicited continuous emission of metals which pose a great threat on human health. Soil samples from 19 station (include control) in Perlis obtained in triplicates and at depths of 0 to 15, 15 to 30, 30 to 45, 45 to 60, 60 to 75 and 75 to 90cm. 7 metals (Pb, Cu, Zn, Cr, Co, Ni and As) was analysed using microwave digestion to determine the concentration and distribution of heavy metals in soil of Perlis. The results with Pb (12.6), Cu (13.8), Zn (157.9), Cr (94.9), Co (3.4), Ni (197.7) and As (19.6) mg/kg exceed the control values. As compared with allowable limit set for soils from the Department of Environment and World Average Soil Value, Pb, Zn, Cr, Ni, As relatively higher. This indicates that the anthropogenic activities and reaction between soil properties and metal affected the soils in the study area greatly. Most soil samples high in surface soil (0-15cm) and decrease from first depth to third and increase from third depth to sixth depth. The mobility of heavy metals largely depended on the role of soil properties such as organic matter, clay content, nodules formulation of Fe and Mn oxides, metal properties and concentration. Implementation of geostatistical and multivariate analysis successfully grouped metals according to their anthropogenic or natural origin and illustrate the spatial distribution trends confirming the clear contribution of anthropogenic inputs. The results demonstrate that groups Pb, Zn and Co probably deposited by vehicular emission. Meanwhile, Cr, Cu, Ni and As were impacted by mixed sources (anthropic and natural origin). Geoaccumulation index and enrichment factor results moderate contaminated to extreme contaminated for Zn, Cr and Ni, while pollution load index has resulted a moderate pollution in station 3, 5, 6, 7, 12, 13 and 18. Findings of this study will create awareness and offer undertaking appropriate action to protect soil quality.